2005
DOI: 10.1159/000090234
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Randomized Pilot Study of Azithromycin and Doxycycline Efficacy and Tolerability in the Treatment of Prostate Infection Caused by <i>Ureaplasma urealyticum</i>

Abstract: A total of 1,442 patients with symptoms of chronic prostatitis were examined over a 4-year period at the Outpatient Department for Urogenital Infections, University Hospital for Infectious Diseases Dr. Fran Mihaljević, Zagreb, Croatia. The inclusion criteria for chronic prostatitis caused by Ureaplasma urealyticum were the presence of clinical symptoms, presence of U. urealyticum in expressed prostatic secretion (EPS) or voided urine collected immediately after prostatic massage (VB3), absence of U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…However, our findings are similar to a more recent trial of men with prostatitis attributed to undifferentiated Ureaplasma, with rates of persistent detection of 22% and 26%, respectively. 18 Consistent with both previous studies, we found little difference in the efficacy of the two therapies for UU-2, suggesting that either treatment is an appropriate first-line regimen for men with UU-2-associated NGU. However, among men with UP, persistent detection was somewhat more common among men who received azithromycin compared with those that received doxycycline.…”
Section: Discussionsupporting
confidence: 91%
“…However, our findings are similar to a more recent trial of men with prostatitis attributed to undifferentiated Ureaplasma, with rates of persistent detection of 22% and 26%, respectively. 18 Consistent with both previous studies, we found little difference in the efficacy of the two therapies for UU-2, suggesting that either treatment is an appropriate first-line regimen for men with UU-2-associated NGU. However, among men with UP, persistent detection was somewhat more common among men who received azithromycin compared with those that received doxycycline.…”
Section: Discussionsupporting
confidence: 91%
“…The eradication rates for azithromycin and clarithromycin were high and similar: 80 (75). Similar results were obtained in CBP caused by U. urealyticum (76).…”
Section: Clinical Evidence Of Efficacy Of Macrolides In Prostate Infesupporting
confidence: 79%
“…The inclusion criteria for chronic prostatitis caused by U. urealyticum were the presence of clinical symptoms, presence of U. urealyticum in EPS, or voided urine collected immediately after prostatic massage. In the group of patients with prostate infection caused by U. urealyticum, the eradication rate was not significantly different when treated with azithromycin (25 of 32 patients) or doxycycline (23 of 31 patients) [23].…”
Section: Mycoplasma Infectionmentioning
confidence: 85%